Automated essay grading system / Chong Theng Hui - Chong , Theng Hui (2005)
Automated Essay Grading System is a web-based assessor for History subject. It is designed and developed for the local History teachers and their students. One of the special feature is this system is Malay language oriented. Teacher who is a grader can upload his question together with a model answer into the database. Students then can use the system to do some exercises or sitting for test. Moreover, the outcome of the result will be known by the student as soon as he or she finished the test. Nevertheless, the development of this automated essay grading system is aim to enhance the information retrieval research on the Malay language stemmer through the indexing module of the system. Hence many researches had been carried out to study exi ting worldwid automated essay grading system. Generally, this system is built using the next generation of programming methology, i.e. ASP.NET wtih Visual Basic.NET as its backbone. This automated essay grading system is developed using modified classical analysis methodology, i.e waterfall model with prototyping. It is not only enhancing the old waterfall model, but also giving us a good system development life-cycle model. Besides, the automated essay grading system has a database which constructed on a client-server architecture basis. In Conclusion this automated essay grading system should give a good impact in the local AI research filed in Malaysia, instead playing the role of a machine that replace the human grader only.